2013
DOI: 10.1590/s1808-16572013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e aspectos sanitarios de bezerras leiteiras que receberam dieta com ou sem medicamentos homeopaticos

Abstract: ABSTRACT:The objective of this study was to evaluate the development of the body, the dry matter intake (DMI), feed conversion (FC) and some sanitary aspects of 12 female dairy calves which were fed with or without the use of homeopathic medicines, from birth to 120 days of age. Newborn crossbred heifers (¾ Holstein x ¼ Gyr) with live weight of 35.71 kg were distributed in a completely randomized design, with six replicates per treatment. During weaning (0 -56 days old), the treatments consisted of milk, being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
2
0
3
Order By: Relevance
“…Em experimentos realizados na região de Feijó, SP com o uso de homeopatia (Fator C&MC ® ) 1 observou-se redução no número de pulverizações para berne e mosca-dos-chifres de 1 banho/mês para 1 banho/ano [5]. Entretanto, não encontraram efeito positivo de produtos homeopáticos no desempenho e na redução de infestação por ectoparasitos [37,38]. É preocupante para esse tipo de aplicação a quantidade utilizada para cada animal, pois normalmente está abaixo ou acima das doses recomendadas para o produto atuar de maneira eficiente [34].…”
Section: Discussionunclassified
“…Em experimentos realizados na região de Feijó, SP com o uso de homeopatia (Fator C&MC ® ) 1 observou-se redução no número de pulverizações para berne e mosca-dos-chifres de 1 banho/mês para 1 banho/ano [5]. Entretanto, não encontraram efeito positivo de produtos homeopáticos no desempenho e na redução de infestação por ectoparasitos [37,38]. É preocupante para esse tipo de aplicação a quantidade utilizada para cada animal, pois normalmente está abaixo ou acima das doses recomendadas para o produto atuar de maneira eficiente [34].…”
Section: Discussionunclassified
“…In a stable test, Signoretti et al (2010) observed weight gain in crossbred dairy cows that received commercial homeopathic products, daily in the concentrate for nine months, without the need to use allopathic products during this period. In another study, however, Signoretti et al (2013) evaluating the body development of dairy calves, from 0 to 120 days of age, who received a diet with or without the use of a commercial homeopathic medicine, did not observe any significant influence on the animals' body development when they added homeopathy to the diet. Figueiredo et al (2018), in a stable test, evaluated the effectiveness of the homeopathic biotherapeutic preparation 30 CH + Sulfur30 CH, in the control of ticks in taurine dairy cows for 12 months.…”
Section: Arqmentioning
confidence: 91%
“…Vet. Zootec., v.73, n.5, p.1001-1013, 2021 Signoretti et al (2013) reported a 90% reduction in the use of ticks in a group of calves treated with homeopathy compared to an untreated group. However, Figueiredo et al (2018) using a 30CH biotherapeutic did not find significant differences in infestation in relation to the control group.…”
Section: Arqmentioning
confidence: 99%
“…Quando perguntados se utilizavam alguma alternativa a produtos químicos, 32,5% (13 produtores) responderam que sim, e destes, 8 (61,5%) usavam produto comercial homeopático. Signoretti et al (2008Signoretti et al ( , 2010Signoretti et al ( , 2013 demonstraram que é viável o uso exclusivo de produtos homeopáticos na pecuária leiteira, em diversas categorias, sendo uma alternativa interessante para os produtores de leite, que deveria ser melhor divulgada, pois muitos deles ainda desconhecem não só os efeitos positivos da homeopatia no controle do carrapato, como de outros produtos alternativos. Um produto a base de alho no sal estava sendo usado por 3/13 produtores (23%), e, a torta de Neem, por 2/13 (15,3%).…”
Section: Quadro 3 Características Das 40 Propriedades Do Município Dunclassified